Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 7 - Algebraic Fractions - Chapters 1-7 Cumulative Review Problem Set - Page 324: 7



Work Step by Step

We evaluate the expression by substituting $x=-6$ throughout the expression and simplifying: $\frac{x^{2}+2x}{x^{2}+5x+6}$ =$\frac{(-6)^{2}+2(-6)}{(-6)^{2}+5(-6)+6}$ =$\frac{36-12}{36-30+6}$ =$\frac{24}{6+6}$ =$\frac{24}{12}$ =$2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.